Funding the New Biologics – A Health Economic Critique of the CCOHTA Report: Infliximab for the Treatment of Crohn’s Disease - Craig R Mitton (Canadian Journal of Gastroenterology)
The report of the Canadian Coordinating Office for Health Technology Assessment (CCOHTA) on the use of infliximab in the treatment of refractory Crohn’s disease stated that the medication did not meet ‘conventional standards of cost-effectiveness’. It had several methodological weaknesses, however, including the derivation of the quality-adjusted life-years (QALYs) gained and the interpretation of the incremental cost utility ratios (ICURs). The validity of economic analyses is highly dependent on the underlying assumptions that are made about the implications of health care states and treatments. The authors of the report mapped utilities from three health states, taken from an American study, onto the nine health states that were considered in their economic analysis. The QALYs that were derived might not have been sensitive to small changes in health outcomes. Moreover, the indirect costs of Crohn’s disease and its complications were ignored. Therefore, it is possible that the benefits of infliximab therapy were underestimated. The high ICURs that were quoted in the report do not necessarily mean that infliximab is not valuable, because opportunity costs were not considered. Instead of calculating the ICUR, a preferable approach would be to determine the benefit of this therapy, compared with that which could be derived from alternative uses of the same amount of health care resources. A ‘balance sheet’ approach would allow decision-makers to determine whether the additional cost of infliximab therapy would be justified by the health care gains that it produces. It is inappropriate to assign an arbitrary cut-off point to cost effectiveness, as defined by ICURs, especially when considering new and expensive treatments for severely ill patients who have few other therapeutic alternatives. Because only a small number of patients would require infliximab, the overall expenditure that would be required to make it available may be manageable.